(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Ischemic Heart disease (IHD) is a common cardiac disorder and is the no.1 cause of mortality and morbidity worldwide. Associated Chronic Kidney Disease (CKD) may further affect the outcome of acute ST elevation myocardial infarction adversely. So, Effective risk stratification is integral to the management of patients with acute coronary syndromes with a co-morbidity of CKD. This observational study was conducted to evaluate the clinical outcome of patients with acute ST Segment Elevation Myocardial Infarction (STEMI) with impaired renal function. Materials and methods: The study was done in the Department of Cardiology, Chittagong Medical College from January 2015 to December 2015. 100 STEMI patients diagnosed by clinical, biochemical and ECG criteria were included in the study. Biochemical and clinical parameters were obtained from eligible subjects. Data was analyzed by computer based software SPSS- 17. Results: Mean ages of patients were 51. 4 years ± SD- 9.54 years. Male to female ratio was 3.34:01. 97% patients were presented with chest pain and breathlessness was found in 65% of patients. Among 100 patients 73 had arrhythmias, 21 were found to develop heart failure, 14 were having cardiogenic shock and death occurred in case of 4 patients. Conclusion: Early detection and appropriate management of renal impairment is necessary to avoid increased mortality and morbidity in STEMI patients. JCMCTA 2018 ; 29 (1) : 5-10